Understanding large-scale deforestation in southern Jinotega, Nicaragua from 1978 to 1999 through the examination of changes in land use and land cover - Zeledon, Esther B.; Kelly, N. Maggi (Journal of environmental management, 2009)
Nicaragua, home to the largest remaining extent of rainforest in Central America (total surface area) and to a significant indigenous population, has lost approximately half of its forest cover since 1950. This major and rapid loss of forest cover has been explained as the consequence of an eastward moving agricultural frontier that cuts through the region of Jinotega. If the current deforestation rate continues, the country could lose its remaining forest cover over the course of the next two decades; therefore, it is essential that the dynamics and relationships of land-use and land-cover change (LUCC) in this region are understood. To examine LUCC in Nicaragua over time, Landsat imagery from the southern portion of the region of Jinotega, taken in 1978, 1987, and 1999 was utilized. A remote-sensing method, supervised classification, which allows for the grouping of spectrally similar values for each year, followed by an image change detection analysis (postclassification comparison) was conducted. Groundtruthing (field validation) was conducted in 2006 to validate the data, which yielded increasing overall accuracy rates of 71.68% for 1978, 82.35% for 1987, and 84.38% for 1999. The classification and change detection results showed that if the agricultural cultivation overtook this region, it happened before 1978. Therefore, the possibility that either deforestation did not actually occur along an agricultural frontier or that it was located further east exists; this would be an interesting subject for future studies. There was, however, clear evidence of increased forest cover from 1987 to 1999 near the urban center, correlating with the enforced reforestation law in the city of Jinotega.